Ethno-Medicinal Uses of Wild Edible Fruits in Pokhara Valley, Nepal (Prithvi Academic Journal, 2022)
The wild fruits are freely available as a source of food. The phytochemicals available in such fruits can be used to cure different health problems of human beings naturally. This study was carried out from July 2020 to August 2021 in different places, particularly in less populated areas like Ward No. 19, 21, 22, 23, 28, 29, 30, 31, 32 and 33 of Pokhara Metropolitan City in Kaski District, Nepal. The data were collected, using a verbal questionnaire in which the respondents were locals and traditional healers. The study was conducted almost in a rural condition, but there was still a good vegetation in its core town areas. People of these areas consume wild fruits mostly as a source of nutrition, vitamins and minerals, but they take them as raw food and know less about their medicinal values. Some wild fruits like Berberis aristata (Chutro), Citrus limon (Jyamir), Cassia fistula (Rajbrikshya), Mangifera indica (Anmp), Punica granatum (Anar), Sapindus mukorossi (Rittha), Tamarindus indica (Imili) and Ziziphus jujuba (Bayar) show their tremendous medicinal values to cure various health problems. Similarly, there are other well-known fruits like Aegle marmelos (Bel), Emblica officinalis (Amala), Piper longum (Pipla), Solanum nigram (Jangali bihi), Terminalia bellerica (Barro) and T. chebula (Harro), which can be used for herbal medicines. The results revealed that 41 species of plants belonging to 24 families have been used as the wild fruits with ethno-medicinal values. Such families are Anacardiaceae, Berberidaceae, Bignoniaceae, Caesalpinaceae, Combretaceae, Elaeagnaceae, Elaeocarpaceae, Euphorbiaceae, Juglandaceae, Lauraceae, Moraceae, Myricaceae, Myrsinaceae, Myrtaceae, Papillionaceae, Piperaceae, Punicaceae, Rhamnaceae, Rosaceae, Rutaceae, Sapindaceae, Solanaceae, Trapaceae and Vitaceae. This study is the first report to show the ethno-medicinal uses of wild edible fruits in Pokhara valley, Nepal.